Examining Teachers' Perceptions of E-Learning Tools: A Survey from Indonesian EAP Classrooms - Suherman, Andri; Wathoni, Hamzani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
Given the fact that online teaching has been widely implemented across the globe during this Covid-19 pandemic, teachers are required to have a high level of IT skills to be able to conduct online teaching. It is without exception that EAP (English for Academic Purpose) teachers need to familiarize themselves with electronic devices due to the benefits they have to offer in an e-learning environment. The current study aims at examining teachersâ€™ perceptions of using e-learning tools in the context of Indonesian EAP classrooms. Forty-five Indonesian EAP teachers participated in the current study with different ages, academic backgrounds, and lengths of EAP teaching experiences. The instruments used to collect the research data were an online survey and semi-structured interviews. The results showed that video and VLEs were the two most commonly-used e-learning tools among the teachers with â€œself-taughtâ€ and â€œcolleaguesâ€ being the two most favorite approaches the teachers have employed to learn such tools. Besides, promoting student engagement and developing learner autonomy were perceived as positive impacts of using e-learning tools by the teachers. Pedagogical implications of this studyâ€™s findings suggested that school authorities should organize more regular pre-service teacher training programs with the purpose to help novice teachers to improve their IT skills. Besides, e-learning tools should be more used in online teachings due to the benefits they have to offer for promoting student engagement and facilitating learner autonomy. A number of limitations in the current study are also presented along with some suggestions for future studies